Analyzing heart sound and murmurs using signal analysis technique - Sarian, Ahmad Mokhzani (2001)
The project paper presents the analysis of sound of the heart and murmurs by using cross correlation technique. This heart sound can yield important diagnostic information and are measured non-invasively. The current practice among the physician to determine the condition of the heart is using an instrument called stethoscope. The effectiveness of this technique depends largely on skills, experiences and the hearing ability of the physician. From a study of the characteristic of the heart sound and human hearing capabilities, it is seen that only highly trained ears may detect heart sound events. It has been shown that using this new technique, the separation between the normal and abnormal subject can be easily obtained. The analysis is done by using MAT LAB mathematical software.